Synthesis, Structure and Properties of an Extra‐Large‐Pore Aluminosilicate Zeolite NUD‐6. Issue 71 (19th November 2020) - Zi, Wenwen; Cai, Xianshu; Jiao, Feng; Du, Hongbin
Abstract: Pure silica zeolites possessing uniform micropores, large surface area and high thermal and chemical stability have been widely studied and used in the fields of fine chemicals and oil industry. The incorporation of aluminium into the framework of silica zeolites changes their properties, making them more industrially useful as adsorbents and catalysts. Herein, we report the synthesis and characterization of an extra‐large‐pore aluminosilicate zeolite NUD‐6 with a 16‐membered‐ring pore channel. Aluminium was directly incorporated into the zeolite NUD‐6 framework, as confirmed by 27 Al MAS NMR studies and ammonia temperature‐programmed desorption probes. Al‐NUD‐6 was not stable when heated at 550 °C to remove the organic templates. However, the organic templates in Al‐NUD‐6 could be removed by oxidation in nitric acid at room temperature. The obtained Al‐NUD‐6H retained the crystalline structure and possessed both micropores and mesopores despite the occurrence of severe structural distortions due to the presence of the corner‐sharing Q 3 Si2 O7 units. The incorporation of aluminium resulted in both medium and strong acid sites in Al‐NUD‐6H, and could facilitate its use in adsorption and catalysis. Abstract : Relax and pores : Extra‐large‐pore aluminosilicate zeolite Al‐NUD‐6 with a 16‐membered‐ring pore channel was synthesized. Removal of the organic templates in Al‐NUD‐6 resulted in a distorted pore structure due to structure relaxation. The incorporation of aluminium resulted in both medium and strong acid sites in Al‐NUD‐6H, implying its potential use as an acidic catalyst.